Pelayanan Pastoral Berfokus pada Kebenaran Injil Sebuah Tinjauan Hermeneutika - Laurensius Sutadi; Carolus Borromeus Mulyanto (Jurnal Orientasi Baru, 2009)
Pastoral ministry is centered around an activity of sharing Gospel values. Itsmain context is faith experience of the people of God. How can these valuesbe truly integrated into ones life? Life of a person is marked by a gradualtransformation. Ones pre-understandings are mainly formed through daily lifepractices. Unavoidably these pre-understandings are assumed in understandingthe Gospel. Hermeneutics unfold a process of understanding. However, thisdoes not mean that a reader would not be able to involve personally andtotally in an effort of living the Gospel. In its turn his or her experiencewill be re-interpreted and transformed by the Gospel. While doing pastoralministry, one and a community will deeply experience the truth of the Gospel.In some ways, they reflect the truth of the Gospel that are peace and justice.The core of pastoral ministry is to foster the living community in promotingthe values of the Gospel. This community may eventually become a peacefuland prophetic movement in the world.